Solve dilemma of corporate sustainability: Research within Indonesian F&B companies - Evelyn Indriani; Eka Pria Anas (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Thrilled by changes in consumer behavior patterns and increased community awareness, Corporate Sustainability (CS) to minimize the environmental impact of business activities, is becoming an increasingly important discussion in Indonesia. However, CS is said to be resting on a dilemma between ethical obligations towards society versus economic duties of maximizing profits. As CS generates new stakeholder expectations towards the organization, company should take real action to solve dilemma.  Research suggests that a company should have Strategic Communication (SC) that is built based on negotiation, understanding, and take into consideration “connections and responsibilities to a larger society” while launching CS. This SC will reinforce key proxy elements for successful CS and increased Corporate Performance (CP). Align with the Regulation of Indonesian Minister of Environment 75/2019, this research focused on the company's responsibility to manage plastic waste which includes reduction, collection, reuse, and recycling. The unit of analysis is F&B companies as one of the largest economic contributors in Indonesia but is also responsible for a variety of different environmental impacts. Quantitative data collection through online questionnaires processed with Partial Least Square (PLS) 3.0. The results show that even though company has made CS as one of the work programs, formed a division to handle CS, as well as awareness of changes in consumer behavior, they acknowledge the lack of SC. By proposing a set of conceptual principles that merge theory and practice, results expected to develop answers to the question: how best to communicate CS thereby contributing to the improvement of the CP?